A new Permian temnospondyl with Russian affinities from South America, the new family Konzhukoviidae, and the phylogenetic status of Archegosauroidea. (4th March 2017) - Pacheco, Cristian Pereira; Eltink, Estevan; Müller, Rodrigo Temp; Dias-da-Silva, Sérgio
Abstract : A new Permian temnospondyl from South America is described and considered to represent a new species – Konzhukovia sangabrielensis sp. nov. – of the genus Konzhukovia previously recorded exclusively from Russia. It consists of the anterior half and partial right side of the skull roof and palate. A comprehensive phylogenetic analysis was performed with several archegosauroids and other well-supported groups of temnospondyls in order to access the affinities of the new Brazilian species and test the monophyly of Archegosauroidea. Archegosauroidea was not recovered as a monophyletic group, comprising successive paraphyletic taxa. The only monophyletic group of 'archegosauroids' is the 'Tryphosuchinae' (in a sister-group relationship with Stereospondyli), composed of Tryphosuchus paucidens, Konzhukovia vetusta, K. tarda and K. sangabrielensis. As the diagnosis of T. paucidens is unclear and based on incomplete material, nested among three species of Konzhukovia, we consider this taxon to be a nomen dubium and purge it from the strict consensus tree. An alternative solution would be to erect a new taxonomic combination for T. paucidens. In order to solve these taxonomic problems, it is necessary to discover more complete material with a clear set of diagnostic characters, to either revalidate this taxon or provide a new combination for it. The phylogenetic results support the erection of a new family – Konzhukoviidae – to replace 'Tryphosuchinae' and accommodate Konzhukovia vetusta, K. tarda and K. sangabrielensis, the new Brazilian species basal to the Russian forms. An early diverging konzhukoviid in Gondwana leads to interesting insights regarding the evolution of the new family, stereospondyl origins, their early diversification and their palaeobiogeographical patterns of distribution. http://zoobank.org/urn:lsid:zoobank.org:pub:4772DC7E-C427-4F5F-89FD-9E68E3B0BFD5